Editor's Note: New directions for Labour/Le Travail = Note de la rédaction : Nouvelles orientations pour Labour/Le Travail - Smith, Charles W.; Sangster, Joan (Labour / Le Travail, 2017)
Announces the co-editorship of Charles Smith and Joan Sangster for this volume, and gratefully acknowledges the work of former editors as well as funding from OPSEU. The journal is a joint partnership of the Canadian Committee on Labour History and the Canadian Association of Work Studies. Seeks submissions that reflect new directions in the study of the workplace and labour, including analyses of labour and the state, feminist political economy, strikes and workplace conflict, union renewal, new models of worker organizing, environmental justice, Indigenous struggles inside and outside the workplace, global workers’ movements, anti-racism campaigns, lgbtq2s struggles. Also welcomes contributions on the social world of work, e.g., popular and working-class cultures, the gendered and racialized experiences of workers, the intersections between colonialism and labour, and the many permutations of labour in the past and present – informal, paid, unpaid, coerced, voluntary.